Evaluating Efficiency, Effectiveness, and Consistency in Goods Procurement Standard Operating Procedures: A Case Study of the Purchasing Department at The Oberoi Beach Resort, Bali - Ni Ketut Ayu Ulan Sari; Wayan Suryathi; I Nyoman Hendra Laksmana (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
This study aims to analyze the implementation of efficiency, effectiveness, and consistency in the Standard Operating Procedure for goods procurement in the purchasing department of The Oberoi Beach Resort, Bali. This research employed a descriptive qualitative approach, with data collected through semi-structured interviews, observation, and documentation. The informants included parties directly involved in procurement activities, namely the Purchasing Manager, Purchasing Supervisor, Purchasing Staff, Receiving Staff, and user departments. Data were analyzed through data reduction, data display, and conclusion drawing and verification. The findings show that the goods procurement SOP has been implemented in a structured manner through Purchase Requisition submission, document approval, Purchase Order issuance, supplier ordering, and goods inspection by the receiving department. The SOP is effective in supporting hotel operational needs and relatively consistent because control stages are maintained even under urgent requests. However, efficiency has not been fully optimized because administrative and approval processes still rely on a manual paper-based system. Other barriers include inventory data input errors, supplier stock limitations, customs constraints, and weather-related distribution disruptions. This study recommends the implementation of e-procurement, stronger interdepartmental coordination, improved inventory data accuracy, and supplier diversification.